2020
DOI: 10.48107/cmj.2020.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance in Trinidad: A population-based survey of adults

Abstract: Objectives: Antibiotic resistance (ABR) is a growing public health issue globally. This study aimed to ascertain the public’s knowledge of antibiotic resistance and to determine any associated demographic factors. Method: A cross-sectional survey was undertaken in Trinidad using a modified version of a World Health Organization questionnaire. Five hundred and fifty participants aged 16 years and older were interviewed. Data were analysed using SPSS Version-22. Results: The response rate was 91% (502/550). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 16 publications
4
2
0
Order By: Relevance
“…Patients receiving a particular antibiotic may experience its side effects regardless of whether they have an allergy to that antibiotic. The overwhelming majority of the surveyed participants in the study of Ali et al 24 and Milani et al 41 understand that antibiotics should only be used when prescribed and that physicians should only prescribe when necessary, which is similar to our findings, where 95.4% understand that antibiotics should only be used with a doctor's prescription.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Patients receiving a particular antibiotic may experience its side effects regardless of whether they have an allergy to that antibiotic. The overwhelming majority of the surveyed participants in the study of Ali et al 24 and Milani et al 41 understand that antibiotics should only be used when prescribed and that physicians should only prescribe when necessary, which is similar to our findings, where 95.4% understand that antibiotics should only be used with a doctor's prescription.…”
Section: Discussionsupporting
confidence: 89%
“…Corollary to our findings, Raupach‐Rosin et al 16 revealed that having a college degree, working as a healthcare worker, and obtaining information from sources such as the internet and newspapers all predict an acceptable level of knowledge and awareness about antibiotic use. A study in Trinidad and Tobago discovered that educational attainment is a predictor of antibiotic use, 24 correlating with our findings. Individuals who are more educated are more aware that an antibiotic‐resistant infection cannot occur if they follow their doctor's antibiotic prescription 24 .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations